Yes, you can! It's easy! Lemme remind you this stuff:

3x -y = 5

… Wait this is wrong. 0.o You need a y equation since it's a system... *checks site she stole it from* Ah. Here it is:

x + y = 11

3x - y = 5

Yeah. First you pick which one you want to solve it with: x or y using the first equation for that. Either one is ok. If you pick x, the equation will turn into:

x + y = 11

=> 11 - x = y

If you pick y it'll be

=> 11 - y = x

Now you pick one of the the above and you put it in your second equation as in:

Let's pick the one that equals y.

3x - y = 5

=> 3x - (11 - x) = 5

=> 3x - 11 + x = 5 ( - changes into + cuz **-** and **( - )** turns into +

we pick here the known and unknown numbers and so we have:

=> 3x + x = 5 + 11 (since -11 changes sides it turns into +)

=> 4x = 16

=> x = 16/4

=> x = 4

Tadaaa! 8D (hoshiz I remember this crap?!)

Second one:

2x +9= 17

2x = 17 - 9

2x = 8

x = 8/2

x = 4

(this one I came up with XD)